Qing dai xi qu zhong de Ming shi zai xian - Hua, Wei (Zhonghua shu ju, 2019)
Detailed summary in vernacular field
Keywords: Geschichte 1368-1911; Chinese drama / Qing dynasty, 1644-1912 / History and criticism; Chinese drama; Qing Dynasty (China); Drama; Chinesisch; China / History / Ming dynasty, 1368-1644; China